Using the Pharmacist Interaction Tracking Tool for Capturing Student-Patient Interactions in Direct and Simulated Patient Care Activities - Hall, Deanne L. (Am J Pharm Educ, 2016)
Objective. To create and implement a standardized data collection tool for capturing student-patient interactions in direct and simulated patient care activities. Design. Faculty members and students determined key elements, design, and an implementation plan for the tool, which was to be used by students across professional years to quantify numbers and types of interactions with patients for tracking student progression toward achievement of curricular outcomes. Assessment. During the 2013-2014 academic year, 27 778 entries were completed, with 17 767 (64%) advanced pharmacy practice experiences, 7272 (26%) introductory pharmacy practice experiences, and 2739 (10%) simulation. Direct patient care interactions occurred with 11 090 patients and 10 983 providers, with 14 252 drug-related problems identified. Data was used by students for their professional portfolios, by administrators for curricular assessment, and to student impact on patient care. Conclusion. The PITT Form enabled the collection of data from actual and simulated patient care activities, allowed for curricular assessment of activities across years, and was used by individual students.